POLITIK PENGELOLAAN HAK BERSAMA (Dinamika Relasi Kuasa Dalam Pengelolaan Perkebunan Karet Rakyat Melalui Lembaga Kesejahteraan Desa Di Desa Kemuja Kecamatan Mendo Barat Kabupaten Bangka) - , Muhammad Anshori ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This thesis entitled of âThe politics of managing commons rights, the dynamic of power relation in managing the collective rubber farm (PKR) through village welfare institution (LKD) in Kemuja village of Mendo Barat sub district of Bangka regencyâ comes from a substantial problem about how do Kemuja people manage the collective rubber farm through LKD institution in the midst of much obstacles both internal problem and shaded by strongly domination and penetration of actors interest who make use of PKR LKD as sphere and arena for persisted contest of power. Because of that, this research aims to answer the question of âhow does the dynamic of power relation in managing the collective rubber farm (PKR) through village welfare institution (LKD) in Kemuja village of Mendo Barat sub district of Bangka regencyâ? To answer that question, this research uses the method of descriptive survey. Using that method, this research at least is able to answer that the dynamic of power relation in managing the PKR through LKD in Kemuja village seems from two things those are from constructed process of PKR LKD as a physical world, a community, and rules-in-use